Hiérophanie et sotériologie dans les traditions ismaéliennes du sous-continent indo-pakistanais - Michel Boivin (Université de Provence, 2000)
Around 1845, Hasan 'Alî Shâh, who was the divine guide (imam) of the Ismailis, took refuge in the Indian subcontinent. To his Indian followers, the Khojâhs, he emphasized his filiation with imam Husayn as a way of legitimizing his statute of saviour, all the while favoring the development of the Shii rituals of Moharram. His successor, 'Alî Shâh, carried on this pursuit of creating Amîr Pîr with which he tried to associate the proper identity of the Ismailis. But, Sultân Muhammad Shâh eliminated all intercessors and presented himself as the qâ'im, an individual savior accesible to all here and now.In the religious literature of the Khojâhs (ginân-s), although 'Alî appears as the mahdi, the imam is known as Naklankî, the name given to the 10th avatar of Vishnû, which is not yet revealed for the Hindus. However, In the Northern Pakistan tradition, the imam is the qâ'im who individually saves the believers, this being a condition for the Resurection led by the mahdi, the first imam 'Alî. The Ismailis consequently put individual salvation very much to the fore, even when the final Resurection will happen at an unknown time.